In vitro activities of antimicrobial combinations against planktonic and biofilm forms of Stenotrophomonas maltophilia - Su, Bo-An; Chen, Chi-Chung; Chen, Hung-Jui; Lai, Hsin-Yu; Tsai, Chia-Hung; Lai, Chih-Cheng; Tang, Hung-Jen; Chao, Chien-Ming (Frontiers in Microbiology, 2023)
Objectives: To investigate the in vitro activity of antibiotic combinations against Stenotrophomonas maltophilia isolates and their associated biofilms. Methods: Thirty-two S. maltophilia clinical isolates with at least twenty-five different pulsotypes were tested. The antibacterial activity of various antibiotic combinations against seven randomly selected planktonic and biofilm-embedded S. maltophilia strains with strong biofilm formation was assessed using broth methods. Extraction of bacterial genomic DNA and PCR detection of antibiotic resistance and biofilm-related genes were also performed. Results: The susceptibility rates of levofloxacin (LVX), fosfomycin (FOS), tigecycline (TGC) and sulfamethoxazole-trimethoprim (SXT) against 32 S. maltophilia isolates were 56.3%, 71.9%, 71.9% and 90.6%, respectively. Twenty-eight isolates were detected with strong biofilm formation. Antibiotic combinations, including aztreonam-clavulanic (ATM-CLA) with LVX, ceftazidime-avibactam (CZA) with LVX and SXT with TGC, exhibited potent inhibitory activity against these isolates with strong biofilm formation. The antibiotic resistance phenotype might not be fully caused by the common antibiotic-resistance or biofilm-formation gene. Conclusions: S. maltophilia remained resistant to most antibiotics, including LVX and β-lactam/β-lactamases; however, TGC, FOS and SXT still exhibited potent activity. Although all tested S. maltophilia isolates exhibited moderate-to-strong biofilm formation, combination therapies, especially ATM-CLA with LVX, CZA with LVX and SXT with TGC, exhibited a higher inhibitory activity for these isolates.